2021
DOI: 10.1249/mss.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Skeletal Muscle miRNA Expression after Resistance, High-Intensity Interval, and Concurrent Exercise

Abstract: IntroductionExercise-induced microRNA (miRNA) expression has been implicated in the regulation of skeletal muscle plasticity. However, the specificity and acute time course in miRNA expression after divergent exercise modes are unknown. In a randomized crossover design, we compared the acute expression profile of eight skeletal muscle miRNAs previously reported to be involved in skeletal muscle development, growth, and maintenance after a bout of either resistance exercise (RE), high-intensity interval exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…miRNA expression is modulated both acutely and chronically following exercise ( D'Souza et al, 2017 ; Mooren et al, 2014 ; Nielsen et al, 2010 ; Telles et al, 2021 ; Uhlemann et al, 2014 ; Baggish et al, 2011 ; Banzet et al, 2013 ; Tonevitsky et al, 2013 ; Aoi et al, 2013 ; Sawada et al, 2013 ; Nielsen et al, 2014 ; Baggish et al, 2014 ; Mitchelson and Qin, 2015 ; Russell et al, 2013 ; Gomes et al, 2014 ). For example, miR-133 is canonically expressed in skeletal muscle ( D'Souza et al, 2017 ; Nielsen et al, 2010 ; Telles et al, 2021 ; Mitchelson and Qin, 2015 ; Russell et al, 2013 ) and significantly increased in the bloodstream (i.e., c-miR-133) after an exercise bout ( Banzet et al, 2013 ; Baggish et al, 2014 ; Gomes et al, 2014 ; Mooren et al, 2014 ; Nielsen et al, 2014 ). Interestingly, it was demonstrated that miR-133a expression is significantly reduced in five breast cancer cell lines (MCF-7, MDA-MB-231, BT-549, SK-BR-3, and T47D) compared to a normal breast cell line HBL-100, as well as in human breast cancer tissue compared to adjacent non-cancerous breast tissue ( Cui et al, 2013 ).…”
Section: Acute Vs Chronic Effect Of Exercise Training On C-mirna Expr...mentioning
confidence: 99%
See 3 more Smart Citations
“…miRNA expression is modulated both acutely and chronically following exercise ( D'Souza et al, 2017 ; Mooren et al, 2014 ; Nielsen et al, 2010 ; Telles et al, 2021 ; Uhlemann et al, 2014 ; Baggish et al, 2011 ; Banzet et al, 2013 ; Tonevitsky et al, 2013 ; Aoi et al, 2013 ; Sawada et al, 2013 ; Nielsen et al, 2014 ; Baggish et al, 2014 ; Mitchelson and Qin, 2015 ; Russell et al, 2013 ; Gomes et al, 2014 ). For example, miR-133 is canonically expressed in skeletal muscle ( D'Souza et al, 2017 ; Nielsen et al, 2010 ; Telles et al, 2021 ; Mitchelson and Qin, 2015 ; Russell et al, 2013 ) and significantly increased in the bloodstream (i.e., c-miR-133) after an exercise bout ( Banzet et al, 2013 ; Baggish et al, 2014 ; Gomes et al, 2014 ; Mooren et al, 2014 ; Nielsen et al, 2014 ). Interestingly, it was demonstrated that miR-133a expression is significantly reduced in five breast cancer cell lines (MCF-7, MDA-MB-231, BT-549, SK-BR-3, and T47D) compared to a normal breast cell line HBL-100, as well as in human breast cancer tissue compared to adjacent non-cancerous breast tissue ( Cui et al, 2013 ).…”
Section: Acute Vs Chronic Effect Of Exercise Training On C-mirna Expr...mentioning
confidence: 99%
“…Interestingly, miR-206 transfection and anti-miR-30c silencing inhibit cell growth and increase apoptosis of MCF-7 breast cancer cells. It is noteworthy that miR-206 is also canonically expressed in the skeletal muscle ( Mitchelson and Qin, 2015 ; Telles et al, 2021 ). Collectively, it is plausible to suggest that miRNAs can translocate from the muscle to the bloodstream in response to an exercise bout and regulate gene expression in pathways associated with tumor growth and suppression in breast cancer cells ( Figure 1 ) ( Dufresne et al, 2018 ).…”
Section: Acute Vs Chronic Effect Of Exercise Training On C-mirna Expr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Telles et al [31] compared skeletal muscle miRNA responses in young men to three types of acute exercise protocols; resistance exercise, high-intensity interval exercise, and both resistance and high-intensity interval exercise performed concurrently. They used a targeted approach for the miRNA analysis, selecting 8 miRNAs with known regulatory roles in skeletal muscle development.…”
Section: Skeletal Muscle Mirnasmentioning
confidence: 99%